O curso de Pedagogia/EaD no Oeste do Paraná: uma análise crítica de sua expansão (2005-2019) - Araújo, Patricia Cruz de (2021)
This study aims to analyze the expansion of the offer of the Pedagogy/EAD course in the western region of the State of Paraná, considering the years 2005-2019 as a time frame, and to discuss the premises of the conception of initial teacher education and its precariousness, as well as the depoliticization and devaluation of the teaching work intrinsic to the modality. In addition, it explores what has been demarcating the History of Distance Education in Brazil, its legal references and its consequences in the western region of Paraná, such as the process of expansion of the distance education course in private institutions, the eminent movement to dismantle the public university and the reaffirmation and dissemination of the modality as a profit-making mechanism in line with market interests. From the promulgation of the current LDBEN n° 9.394/96, Distance Education gained legal legitimacy as a teaching modality and, since then, several policies have been created aiming at the initial and continued training of teachers. Accompanying this reality, there is an exponential increase in the number of enrollments and in the number of private institutions offering the Pedagogy/EaD course. Considering this fact, this research sought to examine the expansion process and the conception of teacher education in this course through a bibliographic and documental analysis, using official documents, relevant legislation and the Pedagogical Project as a source of consultation and data collection. Course (PPC). The results of this study revealed a significant increase in the number of private HEIs in West Paraná from 2005, especially those offering distance degrees, triggering, in this context, the consequent expansion of the Pedagogy/EaD course. In addition, it was evidenced that, for various reasons, such as economic and demand/supply, private institutions have stopped offering the Pedagogy course in the classroom format and making it available exclusively in the distance mode. Furthermore, the analysis of the course's curricular proposal made it clear that the conception of teacher education is based on the premise of preparing them technically for professional practice, absorbing the skills and competences necessary to meet the needs of the market. The demands of contemporary capitalism have turned education and all the elements that make it up into a commodity, a negotiable product at the expense of the future of new generations so that, in a near reality, most teachers who will work in Basic Education in schools Public and/or private programs in the west of Paraná will come from distance courses, especially from private institutions. This shows the strength of the movement to dismantle the public university and alerts to the essential need for defense and continuous struggle in favor of public higher education, free, secular, based on teaching, research, extension and quality classroom teaching.